Planting the Flag in Arctic Waters: Russia’s Claim to the North Pole - Nele Matz-Lück (Göttingen Journal of International Law)
With its demonstrative setting of a Russian Flag on the seabed in the Arctic Ocean outside the 200 nautical miles limitation of the continental shelf in 2007 the Russian Federation has fuelled discussions on claims concerning the outer continental shelf by Arctic rim-States. Although the planting of the flag on the ocean floor is irrelevant under international law, it reveals a political attitude that may make agreement and co-operation concerning the different demands more difficult. The disputes on the boundaries of the outer continental shelf cannot finally be settled by the Commission on the Limits of the Continental Shelf or by dispute settlement under the UN Convention on the Law of the Sea but only by agreement amongst the parties themselves.